Queer Rebels Rewriting Literary Traditions in Contemporary Spanish Novels - Smuga, Łukasz (Routledge Studies in Latin American and Iberian Literature, 2022)
Queer Rebels is a study of gay narrative writings published in Spain at the turn of the 20th century. The book scrutinises the ways in which the literary production of contemporary Spanish gay authors - José Luis de Juan, Luis G. Martín, Juan Gil-Albert, Juan Goytisolo, Eduardo Mendicutti, Luis Antonio de Villena and Álvaro Pombo - engages with homophobic and homophile discourses, as well as with the vernacular and international literary legacy. The first part revolves around the metaphor of a rebellious scribe who queers literary tradition by clandestinely weaving changes into copies of the books he makes. This subversive writing act, named 'Mazuf's gesture' after the protagonist of José Luis de Juan's This Breathing World (1999), is examined in four highly intertextual works by other writers. The second part of the book explores Luis Antonio de Villena and Álvaro Pombo, who in their different ways seek to coin their own definitions of homosexual experience in opposition both to the homophobic discourses of the past and to the homonormative regimes of the commercialised and trivialised gay culture of today. In their novels, 'Mazuf's gesture' involves playing a sophisticated queer game with readers and their expectations.